2014
DOI: 10.1017/s0033291714000762
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the prevalence of attention deficit hyperactivity disorder in incarcerated populations

Abstract: BackgroundStudies report the variable prevalence of attention deficit hyperactivity disorder (ADHD) in incarcerated populations. The aim of this meta-analysis was to determine the prevalence of ADHD in these populations.MethodPrimary research studies reporting the prevalence (lifetime/current) of ADHD in incarcerated populations were identified. The meta-analysis used a mixed log-binomial model, including fixed effects for each covariate and a random study effect, to estimate the significance of various risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(192 citation statements)
references
References 54 publications
(60 reference statements)
12
176
0
4
Order By: Relevance
“…Many of these inmates will likely meet diagnostic criteria for ADHD (Young et al, 2014), and in turn will be released from prison and will require community mental health services. Efficient identification in prison may lead to adequate interventions that could prevent adverse functional outcomes for the individual and for society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these inmates will likely meet diagnostic criteria for ADHD (Young et al, 2014), and in turn will be released from prison and will require community mental health services. Efficient identification in prison may lead to adequate interventions that could prevent adverse functional outcomes for the individual and for society.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term adverse outcomes for ADHD have been documented in a wide range of areas, including school and occupational performance (Shaw et al, 2012), interpersonal relationships (Moya et al, 2014) and comorbidity, including conduct disorder, antisocial personality, and substance use (Levin et al, 2004, van Emmerik-van Oortmerssen et al, 2012. Its burden of disease is evidenced by an increased likelihood for serious accidents (Barkley et al, 1993, Chang et al, 2014, earlier mortality rates (Dalsgaard et al, 2015), delinquency and criminality (Gonzalez et al, 2013, Young et al, 2014. Considerable evidence supports an over-representation of youths and adults with ADHD in correctional services.…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit hyperactivity disorder (ADHD) is frequently linked to criminal activities [4,5]. A recent meta-analysis of 42 studies reported an estimated prevalence of 25.5% for ADHD in incarcerated populations [6], without reporting any medication details in the 26,641 included individuals. Compared to the general population, where the estimated pooled global ADHD prevalence in adults is 2.5% [7], this represents a tenfold prevalence rate.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a memory diary and self-monitoring training could be beneficial for memory monitoring [83,84]. Because caregivers and other support system members can make a world of difference, mental health professionals should consider providing education on the topic of confabulation to these individuals [85][86][87][88][89].…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 99%